Investigation of antagonistic activities of actinomycetes isolated from Cuc Phuong and Ba Be National Parks against four plant pathogenic fungi - Thi Van, Nguyen; Thi Ngoc Mai, Dinh; Thi Hoang Yen, Le; Hong Minh, Nguyen; Kim Nu Thao, Nguyen (Vietnam Journal of Biotechnology, 2020)
Fungal diseases are a huge problem in agriculture, causing serious damage to annual crop yields worldwide. In order to control fungal pathogens in plants, using antagonistic microorganisms is a common approach, especially actinomycetes, as biocontrols considered to be very potential and safe for the environment. With the advantage of high levels of biodiversity, Vietnamese actinomycetes are of a valuable resource for finding strains that are capable of biocontrolling fungal pathogens in plants. Thus, in this study, 70 actinomycete strains were isolated from Cuc Phuong and Ba Be National Parks by four different isolation methods including rehydration centrifugation, sodium dodecyl sulfate – yeast extract, dry heating and dilution methods. Of these, 29 strains (41.4%) belong to rare actinomycete genera including Actinoplanes, Acrocarpospora, Dactylosporangium, Kineosporia, Micromonospora, Nocardia, Nocardiopsis and Pseudonocardia, which are rarely studied in Vietnam. Subsequently, 70 actinomycete strains were subjected to antagonistic activity assays against four highly pathogenic fungi in plants including Alternaria sp., Botrytis cinerea, Colletotrichum gloeosporioides and Phytophthora capsici. The results showed that 80.5% of Streptomyces and 31% of rare actinomyces could inhibit the growth of at least one of the four pathogenic fungal strains. Moreover, ten actinmomycete strains were found to be able to inhibit three types of tested fungal pathogens, simutaneously. Especially, four actinomycete strains (VTCC-A-828, VTCC-A-671, VTCC-A-605, and VTCC-A-69), having the highest antagonistic activity against four fungal pathogens Alternaria sp., Botrytis cinerea, Colletotrichum gloeosporioides and Phytophthora capsici, respectively, were selected. The results in this study indicate the great potential application for Vietnam’s microorganisms in the field of plant protection.